CULTIVATING WORK ENGAGEMENT: THE IMPACT OF INTERPERSONAL COMMUNICATION AND BEHAVIOR - Salim, Mufid; Chinmi, Michael; Lumampauw, Andreas; Hariyanti, Nunik; Rusliansyah, Rusliansyah (ASPIKOM Jabodetabek Region, 2023)
This study explores the integral roles of interpersonal communication and behavior in enhancing work engagement within an organizational context, focusing on work motivation as a mediating factor. Grounded in Self-Determination Theory, the research emphasizes the importance of intrinsic motivation fostered by quality interpersonal relationships that enhance employee engagement and well-being. Conducted at the Dinas Tenaga Kerja dan Transmigrasi Daerah Istimewa Yogyakarta (Yogyakarta Special Region Manpower and Transmigration Service), Indonesia, this quantitative study involved 100 employees and employed hierarchical regression analysis to examine the relationships among interpersonal communication, behavior, and work engagement. Findings indicate significant direct and mediated effects of interpersonal dynamics on work engagement, with interpersonal behavior particularly influential. The study underscores the complexity of work engagement dynamics and supports enhancing interpersonal communication and behavior in organizational settings to boost motivation and engagement. These insights contribute to both theoretical understanding and practical applications in workplace management and communication psychology.